Effects of a combined upper- and lower-limb plyometric training program on high-intensity actions in female U14 handball players - Hammami, M.; Ramirez-Campillo, R.; Gaamouri, N.; Aloui, G.; Shephard, R. J.; Chelly, M. S. (Pediatric Exercise Science, 2019)
Purpose: To analyze the effects of a 9-week plyometric training program on the sprint times (5, 10, 20, and 30 m), change-of-direction speed (modified T test and modified Illinois test), jumping (squat jump, countermovement jump, countermovement jump with arms, and horizontal 5-jump test), upper-body strength (right and left handgrip, back extensor strength, and medicine ball throw), and balance (Y and stork balance tests) of female handball players. Methods: Athletes were randomly divided into experimental (n = 21; age = 13.5 [0.3] y) and control (n = 20; age = 13.3 [0.3] y) groups. Training exercises and matches were performed together, but the experimental group replaced a part of their normal regimen by biweekly upper- and lower-limb plyometric training. Results: Both groups improved performance, but to a greater extent in the experimental group compared with controls for 20- and 30-m sprint times ( delta% = 9.6, P < .05, d = 0.557 and delta% = 20.9, P < .001, d = 1.07, respectively), change of direction (T test: P < .01, delta% = 14.5, d = 0.993 and Illinois test: P < .01, delta% = 7.9, d = 0.769), vertical and horizontal jumping (P < .05), all measures of upper-limb strength (P < .001), and left-leg stork balance (P < .001, delta% = 49.9, d = 1.07). Conclusions: A plyometric training program allows female junior handball players to improve important components of their physical performance.